Peran Bahasa Indonesia dalam Membangun Teknologi Telekomunikasi di Mahasiswa Universitas Telkom Surabaya - Hasan, Utari Zulfa; Putri, Sabillah Rahma; Yusuf, Ichsan Maulana; Pratama, Santa Dinda; Hidayatman, Muh Nur; Nurhayati, Eni (LPPM STKIP PGRI Sidoarjo, 2024)
This study explores the role of the Indonesian language in the development of telecommunication technology among students. In the era of the Industrial Revolution 4.0, mastering the Indonesian language well is crucial for students to communicate effectively and efficiently. The research employs a descriptive qualitative method with questionnaires distributed to students to collect data on their experiences and perceptions of using the Indonesian language in learning telecommunication technology. The results show that 73% of respondents have no relevant experience, while 27% state that the use of the Indonesian language in learning telecommunication technology is good and easy to understand. Respondents also emphasize the importance of routine use of the Indonesian language, the selection of vocabulary that aligns with the KBBI (Indonesian Dictionary), and the provision of comprehensive teaching materials. In conclusion, although the majority of students have no relevant experience, the Indonesian language is quite effective in learning telecommunication technology. These findings provide important guidelines for teaching strategies, particularly in developing students' communication skills.